Evaluasi Hubungan Antara Komponen Kebugaran Jasmani dan Risiko Cedera pada Mahasiswa Aktif Berolahraga - Juhanis, Juhanis; Fatoni, Fatoni; Iskandar, Iskandar; Abriadi, Abriadi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
This study aims to evaluate the relationship between physical fitness components and the risk of injury in active students in the Department of Physical Education, Health, and Recreation, Universitas Negeri Makassar. The fitness components analyzed include muscle strength, cardiorespiratory endurance, flexibility, speed, and balance. The study used a quantitative approach with a correlational design. A sample of 60 students was selected through a purposive sampling technique, with the criteria of routinely participating in sports activities on campus. Data collection was carried out by measuring fitness components using standard physical fitness test instruments, as well as structured questionnaires to record sports injury history. Data analysis was carried out using the Pearson correlation test and multiple linear regression to identify the relationship between fitness variables and injury risk. The results showed that there was a significant relationship between balance, balance, and muscle strength with the risk of injury (p <0.05), while cardiorespiratory endurance and speed did not show a statistically significant relationship. These findings emphasize the importance of developing certain fitness components, especially muscle strength, flexibility, and balance, in physical exercise programs to minimize the potential for injury in physically active students.